The macrophages regulate intestinal motility dysfunction through the PGE2 Ptger3 axis during Klebsiella pneumonia sepsis - Yao, Hua; Fu, Xin; Xu, Qian; Li, Tingting; Li, Yao; Kang, Yan; Wu, Qin (Frontiers in Immunology, 2023)
Abstract Introduction: Gut motility dysfunction, the most common complication of post-septic organ dysfunction, depends on immune and neuronal cells. This study aimed to investigate the mechanisms that activate these cells and the contribution of macrophages to the recovery of intestinal motility dysfunction after sepsis. Materials and methods: Postoperative gut motility dysfunction was induced by establishing Klebsiella pneumonia sepsis in mice with selective deletion of neutrophils and macrophages in the gut. The distribution of orally administered fluorescein isothiocyanate-dextran and carmine excretion time were used to determine the severity of small bowel disease. The effect of macrophages on intestinal motility was evaluated after prostaglandin E2 therapy. Results: We found that muscular neutrophil infiltration leading to neuronal loss in the intestine muscle triggered intestinal motility dysfunction after pneumonia sepsis; however, reduced neutrophil infiltration did not improve intestinal motility dysfunction. Moreover, macrophage depletion aggravated gut motility dysfunction. The addition of macrophages directly to a smooth muscle was responsible for the recovery of intestinal motility. Conclusion: Our results suggest that a direct interaction between macrophages and smooth muscle is neurologically independent of the restoration of intestinal dysmotility.